KONSELING SEBAYA PADA KESEHATAN REPRODUKSI REMAJA DALAM KOMUNIKASI INTERPERSONAL - Purwanti, Sri; Wahyu Utami, Syahrida; Latifah, Latifah (Universitas Palangka Raya, 2022)
In this study the approach used is a quantitative approach. The quantitative approach is an approach that relies on data collection in the form of measurement results. The results of this discussion are: 1) Peer counseling in building relationships with the counselee. Building a relationship with the counselee is carried out at the beginning of the counseling meeting, in building a relationship with the counselee, the peer counselor welcomes the client well and the counselor can also perform attending skills which are carried out with the aim that the counselee can feel comfortable and welcome in his presence. 2) Peer counseling helps the counselee in the decision-making process. Peer counselors assist the counselee in the decision-making process on the problems experienced by the counselee. Peer counselors identify what decisions are needed by the counselee, seen from the diagnosis of the problem and describe the advantages and disadvantages of each decision choice and its consequences. 3) Peer counseling evaluates the counselee in carrying out decisions. After making a decision that will help the counselee to solve the problem, it is necessary to evaluate the counselee